Stunting prevention with determining BMI, UAC, haemoglobin (Hb) levels as early detection in adolescent students Muhammadiyah Senior High School Ponorogo West Java - Aida Ratna Wijayanti; Hayun Manudyaning Susilo; Annisa Ridlayanti (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2023)
Background : One of the problems facing adolescent girls (23%) is iron deficiency (iron deficiency anemia) and it is higher than adolescent boys. Anemia in adolescent girls affect physical activity, learning concentration which will affect adolescent girls achievement. Objectives: This study aims to determine Body Mass Image (BMI), Upper Arm Circumference (UAC), and Haemoglobin (Hb) Levels Pre Integration of Fero Sulfate (Fe) Tablets Supplements and to know relationship between BMI and UAC with Hb levels for Stunting prevention in students at Muhammadiyah Ponorogo High School.Methods: The research design carried out was experimental research with an exploratory study approach, pre-experimental study design, the research takes on January to April 2023 in Muhamamdiyah High School Ponorogo. The samples was 54 people. Researchers analyze Hb, BMI, and UAC levels from all study samples and correlate all variables. Results: The results show that BMI 48% (26 people) undernutrition, UAC 65% (35 people) underweight condition and Hb levels showed 87% (47 people) normal. The statistical analysis test shows that p-value test = 0.089 which means that there is no relationship between BMI and Hb levels in adolescent girls. Similarly, Hb levels with UAC show no relationship with p value 0.707.Conclusions: The conclusion of this study, there are still many adolescent girls who experience malnutrition status, although found a few of these samples are anemic. So it is important that future studies on balanced nutritional intake and standardized Fe supplementation for stunting prevention in adolescence are important.